Elaboración y validación de un cuestionarío para medir los niveles de gestión técnica de las empresas de plásticos del Ecuador - España Rosero, María Zulleyka (2009)
At present, companies in the plastics sector are facing serious problems affecting the productivity of this industry, including shortages and rising prices of the resins which constitute the raw material for manufacturing processes for plastics , the long production time in processing, poor planning, inventory management and poor control performance of the machines, this led to the need to design a system of management indicators to monitor and improve their production processes reducing operating costs and increasing their margins and useful. All the above led to a project being undertaken and Aseplas ESPOL, which aims to improve the productivity of this sector. This thesis represents the initial phase of the project, covering the stages of knowledge production processes in the plastics sector Ecuadorian selection of a set of management using the technique of the Balanced Score Card, concluding with the development of a questionnaire designed to measure these indicators effectively and efficiently.